Beam Smoothing Based on Prism Pair for Multistep Pulse Compressor in PW Lasers - Shuman Du; Xiong Shen; Wenhai Liang; Peng Wang; Jun Liu (Photonics, 2022)
Ultra-short, ultra-intense lasers provide unprecedented experimental tools and extreme physical conditions, enabling the exploration of the frontiers of basic physics. Recently, a multistep pulse compressor (MPC) method was proposed to overcome the limitations of the size and the damage threshold of gratings in the compressor for the realization of a higher-peak-power laser. In the MPC method, beam smoothing is an important process in the pre-compressor. In this study, beam smoothing based on prism pairs is investigated, and the spatial profiles, as well as spectral dispersion properties, are analyzed. The simulation results demonstrate that the prism pair can effectively smooth the laser beam. Furthermore, beam smoothing is found to be more efficient with a shorter separation distance if two prism pairs are arranged to induce spatial dispersion in one or two directions. The beam smoothing results obtained in this study will help optimize optical designs in petawatt (PW) laser systems, thereby improving their output and operational safety.